2001
DOI: 10.4049/jimmunol.166.4.2179
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment of Human Peyer’s Patches Inhibits the Increase in CD38 Expression Associated with the Germinal Center Reaction

Abstract: Analysis of B cells in the human tonsils identified CD38 expression as a hallmark of germinal center (GC) B cells. However, the signals responsible for the in vivo induction of CD38 have not been determined. The primary site for generation of memory and plasma cells in the gastrointestinal tract is the GCs of Peyer’s patches (PP). PP and intestinal mucosa, but not tonsils or oral mucosa, express mucosal addressin cell adhesion molecule-1 (MAdCAM-1). The ligand for MAdCAM-1, integrin α4β7, is expressed on naive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…Similar results were obtained with an alternative strategy based on CD138 expression, 18 although this strategy was more difficult to apply to all samples because CD138 was not uniformly expressed on PCs nor was its expression restricted to PCs (data not shown), which is consistent with observations from previous studies on gut samples from HIV-infected patients. 19 Another plasma cell (PC) marker, CD38, also presents difficulties both in the gut 20 and in certain disease settings. 21 Furthermore, the gating strategy was verified by determining the immunoglobulin isotype distribution among the PCs.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained with an alternative strategy based on CD138 expression, 18 although this strategy was more difficult to apply to all samples because CD138 was not uniformly expressed on PCs nor was its expression restricted to PCs (data not shown), which is consistent with observations from previous studies on gut samples from HIV-infected patients. 19 Another plasma cell (PC) marker, CD38, also presents difficulties both in the gut 20 and in certain disease settings. 21 Furthermore, the gating strategy was verified by determining the immunoglobulin isotype distribution among the PCs.…”
Section: Resultsmentioning
confidence: 99%
“…Although tonsillar CD19 ϩ cells represent mainly GC B cells, naive cells are also abundant in the tonsils. 17,18 High expression of KLF4 in naive cells compared with memory B cells has been reported. 9 Thus, we investigated whether low expression of KLF4 in the B lymphomas simply reflects physiologically low levels of KLF4 in their GC progenitors ( Figure 1C).…”
Section: Klf4 Is Epigenetically Silenced In B-cell Lymphomasmentioning
confidence: 99%
“…Recent studies have shown only GC B cells of PP in aged mice have normal activation phenotype, i.e. Unlike tonsil, PP GC B cells do not express high levels of CD38, although they could be induced to do so after CD40L, IFNγ and anti B cell receptor (BCR) activation [103]. Tonsilar GC B cells can be isolated on the basis of CD39 or IgD expression [101].…”
Section: Role Of Igm In Mucosal B Cell Memorymentioning
confidence: 99%
“…high CD80 and CD86 and low CD23, CD62L and CD38, and highly mutated IgM genes [100]. Moreover, ligation of β7 can reduce CD38 expression [103]. Moreover, tonsilar centroblasts are CD77hi while centrocytes are CD77lo [102].…”
Section: Role Of Igm In Mucosal B Cell Memorymentioning
confidence: 99%